Fund fragility: The role of investor base - Nolwenn Allaire; Johannes Breckenfelder; Marie Hoerova (European Central Bank (ECB), 2023)
Using security-by-security data on investor holdings in the euro area, we study run dynamics across different fund-shares of the same fund during the unprecedented liquidity crisis in March 2020. For an average bond or equity mutual fund-share, households, other euro area funds, and the foreign sector each represent about a quarter of the total holdings. Insurance companies hold another 14%, with all other investors combined (banks, non-financial corporations, pension funds, etc.) accounting for less than 10% of holdings. Analyzing bond funds, we show that fund-shares with higher ownership by other funds suffered substantially higher outflows (by 6 percentage points), while fund-shares with higher ownership by households had substantially lower outflows (by 5 percentage points) compared to the other fund-shares within the same fund. This gap is not driven by time-varying differences in fund performance. Results for equity funds are similar, although they faced substantially smaller outflows, coupled with much larger declines in performance, compared to bond funds. Our findings suggest that a collective "dash for cash" by consumers and firms in need of liquidity at the outset of the COVID-19 pandemic was not the source of mutual fund fragility. Instead, the most run-prone investor type turned out to be the fund sector itself.
Keywords: G01; G10; G21; G23; 330; mutual funds; runs; liquidity; investor type; March 2020 liquidity crisis